2011
DOI: 10.4149/neo_2011_05_424
|View full text |Cite
|
Sign up to set email alerts
|

Chemical sympathectomy suppresses fibrosarcoma development and improves survival of tumor-bearing rats

Abstract: Both experimental and clinical data indicate that the sympathetic nervous system may affect the development of certain tumors. To test this, in the present study we combined in vivo and in vitro approaches to study the effect of the sympathetic nervous system on proliferation of BP6-TU2 fibrosarcoma cells. First, we investigated the effect of 6-hydroxydopamine-induced sympathectomy on tumor development and survival of tumor-bearing rats. One week after chemical sympathectomy, we injected the BP6-TU2 fibrosarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 21 publications
1
29
0
2
Order By: Relevance
“…Stimulatory eff ect of the sympathetic nervous system on the tumor growth and development of metastasis has been further supported by experimental and clinical studies, in which sympathetic neurotransmission was attenuated or eliminated (Raju et al 2009;Sloan et al 2010;Barron et al 2011;Lackovicova et al 2011;Magnon et al 2013). Based on these facts, it has been suggested that interventions reducing the eff ect of the sympathetic neurotransmitters may represent a potential adjuvant therapy in oncological patients (Schuller 2010;Powe and Entschladen 2011;Tang et al 2013).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Stimulatory eff ect of the sympathetic nervous system on the tumor growth and development of metastasis has been further supported by experimental and clinical studies, in which sympathetic neurotransmission was attenuated or eliminated (Raju et al 2009;Sloan et al 2010;Barron et al 2011;Lackovicova et al 2011;Magnon et al 2013). Based on these facts, it has been suggested that interventions reducing the eff ect of the sympathetic neurotransmitters may represent a potential adjuvant therapy in oncological patients (Schuller 2010;Powe and Entschladen 2011;Tang et al 2013).…”
mentioning
confidence: 81%
“…sympathectomy, administration of β-blockers) have shown stimulatory eff ect of sympathetic nervous system on several experimental tumors, as well. For example, chemical sympathectomy performed by 6-OHDA attenuated the incidence of N-methyl-N´-nitro-N-nitrosoquanidine (MNNG) induced gastric cancer in rats (Tatsuta et al 1992), inhibited the growth pattern of LPC-1 plasmacytoma tumors in mice (Grzanna et al 1985), and also decreased the incidence of intra-abdominal fi brosarcoma tumors in rats and prolonged their survival (Lackovicova et al 2011). Similarly, bilateral surgical sympathectomy in rats resulted in the development of significantly smaller and less invasive tongue tumors than in sham-operated animals (Raju et al 2007;Raju et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, sympathectomy had no effect on development of tumor metastases in these animals (Romeo et al, 1991). In our previous study we have shown that the chemical sympathectomy significantly decreased the incidence of intra-abdominal fibrosarcoma tumors in male Wistar rats and prolonged their survival in comparison with nondenervated ones (Lackovicova et al, 2011). In another animal study, the treatment with deprenyl, a monoamine oxidase B inhibitor, reduced the age-related spontaneous mammary and pituitary tumor growth (Thyagarajan et al, 1995).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, no effects of sympathectomy occurred when mice were denervated after injection of cancer cells (Brenner et al, 1992). Previously, we showed a direct effect of NE on BP6-TU2 fibrosarcoma cells growth in vitro, when its influence was markedly stimulatory (Lackovicova et al, 2011). Raju et al (2007) have explained the cause of significantly smaller and less invasive tongue tumors in bilaterally sympathectomized rats by the difference in sympathetic innervation pattern within and around the tumors.…”
Section: Groupsmentioning
confidence: 94%
“…Drugs that target stress and anxiety are associated with improved prognosis, including increased survival times [29-32]. Under high stress conditions, sympathetic nerves release additional epinephrine and norepinephrine ( NE ), that has been shown to increase IL-6 and reactive oxygen species, all of which promote cancer cell survival and proliferation [33-36]. In vitro, cancer cell survival and proliferation are effectively inhibited by incubation with adrenergic receptor antagonists [37, 38].…”
Section: Neuroactive Molecules and Cancermentioning
confidence: 99%